ANALISA KATEKESE NARATIF LAGU BERDASARKAN HERMENEUTIKA TEOLOGI NARATIF - Mite, Matheus Beny (CREDENDUM: Jurnal Pendidikan Agama, 2019)
The narrative catechesis has characteristics: change, free, and heal catechetical participants. Narrative catechesis reveals the experience of past life that is long hidden or buried. Thus, narrative catechesis is appreciated as a blessing today and gives hope for the future. From this characteristic, trying to analyze narrative catechesis is not difficult. He should have past experiences rooted in certain cultures. A culture (pre-critical) that is full of values frees every person or community from the idea that only rules / formulas or teachings that are understood by reason alone are correct. It is this culture that has buried the experience of even narrative catechesis. In a general sense, narrative texts always have their own patterns that need to be followed. Therefore, narrative catechesis needs to develop itself in certain cultural contexts and traditions of narrative theology, as a result the analysis of narrative catechesis needs to consider the hermeneutics of narrative theology. Y.B. Metz, a fundamental theologian and political theology, taught us since, 1960s, before the Second Vatican Council and moreover in the 1970s, after (post) Vatican Council II. After the Council, he disseminated narrative theology in various monumental theological essays. Understanding this by interpreting theology will lead us to the determination to build narrative catechesis in an effort to evoke faith from every community/ community in an atmosphere of joy and liberating conversation. Narratives from local culture are not only found in romance, novels, fairy tales and others narrated, but are also found in songs of every culture. Poetry that is attached to a song is often a narrative story that can evoke faith, because the narrative story of the song is born from the experience of the heart (spiritual and emotional development), the feeling and intention (effective and creativity development), intellectual development and (perhaps also) sports and kinesthetic (physical and kinesthetic development)